Seasonal variation in the odour characteristics of whole milk powder - Biolatto, Andrea (2006)
Seasonal changes in whole milk powder odour characteristics were monitored using SPME-GC and E-nose methodologies. ANOVA showed a significant effect of the season on dimethyl sulphide, n-pentanal, n-hexanal, and butyric acid. Whole milk powder manufactured in summer season had significantly (p < 0.05) higher levels of n-hexanal, n-pentanal and dimethyl sulphide as compared to autumn and winter seasons. On the other hand, butyric acid showed significant differences (p < 0.05) among autumn and spring. Applying linear discriminant analysis, seasonal variations in the odour profiles assessed by electronic nose were observed. A better classification outcome was obtained when volatile compounds and electronic nose data were analysed together, obtaining a success rate of 89.5% and 70.7% of the original cases and after cross-validation respectively. As in other application reported in the literature, E-nose approach represents an alternative technique to traditional methods of odour measurement.